FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) PADA IBU YANG MEMILIKI BAYI USIA 0-12 BULAN DI WILAYAH KERJA PUSKESMAS OPHIR PASAMAN BARAT TAHUN 2024 - Yanti, Rahmita; Harleni, Harleni; Dila, Feni Abma (Ensiklopedia of Journal, 2025)
Low Birth Weight (LBW) is a baby born with a weight of less than 2500 grams. Based on WHO 2018 data, the prevalence of BBLR is 15.5% of all births in the world, of which 96.5% occurs in developing countries. The prevalence of LBW at the Ophir Health Center in 2021 was 3.1%, increased in 2022 to 4.1%, and 4.6% in 2023. The purpose of this study is to determine the Factors Associated with the Incidence of LBW in Mothers Who Have Babies Aged 0-12 Months in the Working Area of the Ophir West Pasaman Health Center in 2024. This type of research is cross sectional, the research was conducted in February-August with a population of 425 people and a sample of 58 people. Primary and secondary data collection by researchers with editing, coding, entry, processing, cleaning processing techniques and using univariate and bivariate analysis with chi square test. The results of this study showed that most mothers who had children aged 0-12 months in the working area of the West Pasaman Ophir Health Center gave birth with low birth weight. It was found that most mothers consumed carbohydrates, proteins, fats, which were lacking and nutritional status was poor with a p value of 0.000. Most mothers consume iron and are less knowledgeable with a p value of 0.001, which means that there is a meaningful relationship between carbohydrate, protein, fat, iron, nutritional status, and maternal knowledge consumption and the incidence of LBW. It is hoped that the community, especially pregnant mothers, will pay more attention to their pregnancy conditions and meet the needs of macronutrient and micronutrient intake and pay more attention to nutritional status so that the mother and fetus are healthy and the nutritional needs of the mother and fetus are met.Keywords: BBLR, Corbohydrates, Proteins, Fats, Iron, Nutritional status, Knowledge.